Understanding the harmful effects of sickness presenteeism and emotional labor: implications for the hospitality industry - Leal, Ana Catarina de Almeida Correia (2022)
This thesis aims to examine how the phenomenon of presenteeism (i.e., the act of going to work while ill) affects hospitality organizations' profitability, employee well-being, and the management of emotional labor demands. It comprises three empirical studies. The first study (Chapter 2), explores the impact of presenteeism on hotels’ profitability. The results show that when employees show sickness while providing services, customers show weaker recommendation and return intentions toward tourist accommodations (vs. employees who show no signs of sickness). The second study (Chapter 3), investigates the impact of contextual and personal factors on hotel employees' burnout levels, through the mediating role of surface acting (SA). The results support the indirect effect of SA on the proposed relationships. Also, results of a complementary analysis with a subsample of hotel employees who reported presenteeism exposed that, for them, the “surface acting sickness regulation” strategy proposed by the researchers mediated the relationship between presenteeism climate and burnout. Finally, the third study (Chapter 4) examines the effects between customer incivility and hotel staff sickness on SA and deep acting, showing only positive and significant results for the use of SA strategies. Furthermore, the results highlight that even when dealing with polite and understanding customers, sick employees strive to provide cheerful service, showing higher SA. Especially in this pandemic time when the precariousness associated with the hotel industry has increased, creating an even more prevalent climate of presenteeism, this thesis contributes to understanding why hotel management teams must join forces to create healthy workplaces.